EEG Based Emotion Recognition by Combining Functional Connectivity Network and Local Activations - Li, Peiyang; Zhang, Yangsong; Xu, Peng; Liu, Huan; Si, Yajing; Li, Cunbo; Li, Fali; Zhu, Xuyang; Huang, Xiaoye; Zeng, Ying; Yao, Dezhong (IEEE transactions on biomedical engineering, 2019)
Objective: Spectral power analysis plays a predominant role in electroencephalogram-based emotional recognition. It can reflect activity differences among multiple brain regions. In addition to activation difference, different emotions also involve different large-scale network during related information processing. In this paper, both information propagation patterns and activation difference in the brain were fused to improve the performance of emotional recognition. Methods: We constructed emotion-related brain networks with phase locking value and adopted a multiple feature fusion approach to combine the compensative activation and connection information for emotion recognition. Results: Recognition results on three public emotional databases demonstrated that the combined features are superior to either single feature based on power distribution or network character. Furthermore, the conducted feature fusion analysis revealed the common characters between activation and connection patterns involved in the positive, neutral, and negative emotions for information processing. Significance: The proposed feasible combination of both information propagation patterns and activation difference in the brain is meaningful for developing the effective human-computer interaction systems by adapting to human emotions in the real world applications.